2020
DOI: 10.21203/rs.3.rs-27632/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Three redescriptions in Tintinnopsis (Protista: Ciliophora: Tintinnina) from coastal waters of China, with cytology and phylogenetic analyses based on ribosomal RNA genes

Abstract: Background: The taxonomy of tintinnine ciliates is vastly unresolved because it has traditionally been based on the lorica (a secreted shell) and it has only recently incorporated cytological and molecular information. Tintinnopsis, the most speciose tintinnine genus, is also the most problematic: it is known to be non-monophyletic, but it cannot be revised until more of its species are studied with modern methods. Results: Here, T. hemispiralis Yin, 1956, T. kiaochowensis Yin, 1956, and T. uruguayensis Balech… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…The other complex somatic ciliary patterns hitherto described deviate by minute features (e.g. the starting point of the ventral kinety, the position of the posterior kinety, and the number of dikinetids in the first right kineties; Agatha, 2008, 2010b; Bai et al, 2020c, d; Wang et al, 2020), which might contribute to the necessary revision of the non‐monophyletic genus Tintinnopsis (Agatha & Strüder‐Kypke, 2007). Note that in contrast to the description of T. cylindrica by Agatha and Riedel‐Lorjé (2006), Coats et al (2010) demonstrated that its pattern is similar to that of Schmidingerella in a ventral kinety composed of a monokinetidal anterior and a dikinetidal posterior portion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The other complex somatic ciliary patterns hitherto described deviate by minute features (e.g. the starting point of the ventral kinety, the position of the posterior kinety, and the number of dikinetids in the first right kineties; Agatha, 2008, 2010b; Bai et al, 2020c, d; Wang et al, 2020), which might contribute to the necessary revision of the non‐monophyletic genus Tintinnopsis (Agatha & Strüder‐Kypke, 2007). Note that in contrast to the description of T. cylindrica by Agatha and Riedel‐Lorjé (2006), Coats et al (2010) demonstrated that its pattern is similar to that of Schmidingerella in a ventral kinety composed of a monokinetidal anterior and a dikinetidal posterior portion.…”
Section: Discussionmentioning
confidence: 99%
“…The total genomic DNA was extracted, using the DNeasy Blood & Tissue kit (Qiagen). The PCR amplification of the SSU rRNA gene and ITS1‐5.8S rRNA gene‐ITS2 regions was performed with the primers 18S‐F (5’–AAC CTG GTT GAT CCT GCC AGT–3′) and 5.8S‐R (5’–TAC TGA TAT GCT TAA GTT CAG CGG–3′) (Bai et al, 2020c; Medlin et al, 1988). The PCR amplification of the LSU rRNA gene was performed with the primers 28S‐1F (5’–ACC CGC TGA ATT TAA GCA T–3′) and 28S‐3R (5’–AAC CTT GGA GAC CTG AT–3′) (Moreira et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation